A multifunctional nanoprobe for targeting tumors and mitochondria with singlet oxygen generation and monitoring mitochondrion pH changes in cancer cells by ratiometric fluorescence imaging. Issue 14 (20th March 2020) - Zhao, Jingjin; Zou, Mengbing; Huang, Mengjiao; Zhang, Liangliang; Yang, Keqin; Zhao, Shulin; Liu, Yi-Ming
Abstract : A multifunctional nanoprobe with singlet oxygen generation that can target tumors and mitochondria was developed for photodynamic therapy of tumors and monitoring mitochondrion pH changes in cancer cells by ratiometric fluorescence imaging. Abstract : Mitochondria are the main sites of cell metabolism. Even minor pH changes may lead to mitochondrial dysfunction and promote cell apoptosis. Mitochondrion-targeting photosensitizers can produce singlet oxygen in the mitochondria. In tumor photodynamic therapy (PDT), tumor cells are killed through singlet oxygen generation by photosensitizers, and optimally the process of cell apoptosis can be real-time monitored by monitoring the changes of mitochondrial pH value. To this end, a multifunctional nanoprobe that is not only able to produce singlet oxygen in mitochondria but also able to detect the changes in mitochondrial pH value has been developed in this work. The probe is a single-excited dual-emission biomass quantum dot (BQD-FA) prepared from Osmanthus leaves with folic acid (FA) and polyoxyethylene diamine as modifiers. The BQD-FAs can target tumor cells and mitochondria, and produce singlet oxygen in the mitochondria under near-infrared laser irradiation ( λ em = 660 nm). On the other hand, in the pH range of 3–8, the fluorescence intensity ratio of BQD-FAs at wavelengths 490 nm and 650 nm showed a good linear relationship with the pH value of mitochondria. The ratiometric fluorescence imaging of mitochondria using the prepared BQD-FAs showed that when the cells were chemically stimulated with chlorphenizone, the mitochondrial pH dropped from 7.9 to 7.2 within 15 min. Based on these characteristics, we envision that the prepared multifunctional nanoprobe will be of high significance in the biomedical research of mitochondria and PDT of tumors.